Implementation Building Information Modelling For Construction Projects In Remote and Challenging Locations: (Case Study Road Handling and Bridges Project Toapejat - Rokot - Sioban (Simp. Logpon)) - Sembodo, Priyo (Ridwan Institute, 2024)
This research discusses the innovative implementation of digitalization of infrastructure construction based on Building Information Modelling (BIM) 5D on the Toapejat - Rokot - Sioban Road and Bridge Handling Project (Simp. Logpon) in the Mentawai Islands. The focus is a collection of AEC software from Autodesk, including Revit, Civil 3D, Navisworks, and BIM 360, which supports the project's BIM goals. This method is proven to provide a holistic approach to planning, design, construction, and management of infrastructure projects. In the face of growing competition and innovation of BIM technology, this study emphasizes the need for continuous innovation for construction companies to participate in the development of digital construction technology. The project is considered a clear example of BIM's crucial role in overcoming construction challenges in remote areas, unlocking potential for future projects on isolated islands.